Network Selection Algorithm Based on Weighted Bipartite Graph in Heterogeneous Network Environment - Nan Bao; Weiwei Xia; Xu Bao (Dianxin kexue)
In convergence environment of heterogeneous network, a network selection algorithm based on weighted bipartite graph was proposed for rational utilization of heterogeneous network wireless resource. The network selection process was mapping as looking for the optimal weighted bipartite graph. The requirements of users and networks were mathematically modeled for optimal matching of supply and demand. And there was a second chance of matching to balance the network load. Compared with other algorithms, the proposed algorithm can provide matching results that meet the requirements for different QoS. Meanwhile it can dynamically adjust networks' loads, and achieve reasonable matching of user demands and network resources in convergence environment of heterogeneous network.